Financial accounting in Australia - Hoggett, J. R. (John Robert), 1948- (Milton, Qld. John Wiley & Sons Australia, 2003)
Financial accounting in Australia.
Age Group: Adult
[V.1] text -- [V.2] study guide.
Previous ed.: 2000.
Includes index.
Keywords: Accounting -- Australia; Accounting -- Australia -- Problems, Exercises, Etc